Social support for overcoming fear of contagion at the start of the COVID-19 pandemic. Cross-sectional study in Latin America - Carrillo, Irene; Poblete, Rodrigo; Serpa, Piedad; Martin-Delgado, Jimmy; Giménez, Alejandro; Mira, José Joaquín (Frontiers in Psychology, 2023)
The psychological impact of the COVID-19 pandemic on healthcare professionals has been widely studied, along with different strategies to minimize it. However, professionals' assessment of the social support received and the factors that mitigated their fear of contagion have not been described. This study aimed to assess health professionals' satisfaction with the social support and information received and their efforts to self-isolate to avoid infecting loved ones in Chile, Colombia, and Ecuador. A cross-sectional online survey, conducted from July to September 2020 in three Latin American countries, elicited health professionals' satisfaction with social support from colleagues, their community, the media, and scientific societies; as well as the information received about the evolution of the pandemic and measures to avoid contagion. The EASE scale was used to measure acute stress. Results: Survey responses were received from 700 professionals. The response rate per country exceeded the estimated sample size except in the case of Colombia, which was 81.4%. In general, peer support was highly valued, though satisfaction was lower in high-risk units (p<0.001). Those who directly assisted COVID-19 patients perceived the least community support (p=0.023). Professionals from high-risk units (p=0.013) and those who experienced greater acute stress assigned the lowest rating to the information offered by the centre on the pandemic (p=0.05). Men perceived more support from colleagues and better information from the centre than women (p<0.05). Just 10.7% of professionals changed their residence during the pandemic, but those who worked in high-risk areas self-isolated more frequently (p=0.026). In the early stages of the COVID-19 pandemic, healthcare professionals in Chile, Colombia, and Ecuador greatly valued their peers' support. Being infected with COVID-19, working in high-risk areas, experiencing higher self-reported acute stress, and having an infected co-worker were predictors for self-isolation to protect their relatives. These results highlight the appropriateness of implementing institutional resources based on peer support and specific communication strategies and action protocols to build resilience and responsiveness to future health crises. Peer support was a key element in coping with work overload during pandemic. The perceived risk of contagion decreased the effectiveness of the usual coping resources for acute stress.